2016
DOI: 10.1016/j.joms.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Among Patients With Facial Fractures, Geriatric Patients Have an Increased Risk for Associated Injuries

Abstract: AIs are much more frequent and severe in geriatric patients, and the elderly die more often of their injuries. The results emphasize that elderly patients require specific attention and multi-professional collaboration in the diagnosis and sequencing of trauma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 20 publications
(36 reference statements)
4
22
0
16
Order By: Relevance
“…These specific characteristics of this age group explain the differences found in relation to the traumatic agent and the location of fractures in this group. The most common cause of facial injuries among the elderly was falls, which agreed with other studies 2,6,[9][10][11][12] , although traffic accidents were the most frequent cause of facial traumas among the 60-69 years age group.…”
Section: Discussionsupporting
confidence: 90%
“…These specific characteristics of this age group explain the differences found in relation to the traumatic agent and the location of fractures in this group. The most common cause of facial injuries among the elderly was falls, which agreed with other studies 2,6,[9][10][11][12] , although traffic accidents were the most frequent cause of facial traumas among the 60-69 years age group.…”
Section: Discussionsupporting
confidence: 90%
“…Associated injuries are frequent in geriatric patients . In the present study, the most common concomitant injuries affected the upper (and lower) limbs (41.9%) as well as the neurocranium (34.8%), with a high proportion of cerebral contusion (34.1%) and intracranial bleeding (8.8%).…”
Section: Discussionmentioning
confidence: 49%
“…In this nationwide, large database analysis, falls were the most common cause of facial fracture among the American older adults, as previous studies with smaller, regional samples have suggested . Falls among older adults are considered a public health issue, as fall‐related burden and costs are rising in many countries, placing a substantial economic challenge on society .…”
Section: Discussionmentioning
confidence: 66%
“…6 Among all types of fractures in the older adults population, the prevalence of facial fractures has seen an increase over recent years, 6 and more participation of older adults in recreational activities may be one of the reasons for this increase. 7 Falls are the most common cause of facial fracture among older adults, [8][9][10][11] and older adults are more likely to sustain higher morbidity related to facial trauma, having longer hospital stays, more associated injuries, and even death as a result of their injuries when compared to younger cohorts. 9,10 Important reasons for higher morbidity and mortality among older cohorts include the effects of facial trauma on breathing, swallowing, speech, chewing, and sight, which may impact older adults' functionality and thus independence.…”
Section: Introductionmentioning
confidence: 99%